A new polymorph of 2, 6‐diaminopyridine. Issue 11 (24th October 2017) - Hall, Victoria M.; Bertke, Jeffery A.; Swift, Jennifer A.
Abstract : Sublimation yielded a new polymorph of 2, 6‐diaminopyridine, a common ingredient in and a synthetic precursor to many colorants. Abstract : 2, 6‐Diaminopyridine (26‐DAP, C5 H7 N3 ) is a common intermediate in the synthesis of aromatic azo chromophores, which are widespread in the dyes and pigments industry. Sublimation of commercial 26‐DAP powder yielded a new polymorph, denoted Form II, which grew as colorless orthorhombic needles. Recrystallization from acetone or toluene also yielded Form II as the major phase. Thermal analysis shows that Form II is a less stable polymorph and it converts upon heating at 335 K to the previously reported Form I.